Pengaruh Likuiditas, Profitabilitas dan Leverage Terhadap Financial Distress pada Perusahaan Manufaktur - Riki Adi Saputra; Suprihatmi Suprihatmi; Setyaningsih Setyaningsih (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The aim of this research is to nalyze the significance of the effect of liquidity, profitability, leverage on financial distress in food and beverage subsector companies on the Indonesia Stock Exchange for the period 2019-2023. This study uses quantitative research with a total sample of 10 samples. The results of this study indicate the t test, namely liquidity has a significant effect on financial distress in food and beverage subsector companies listed on the Indonesia Stock Exchange in 2019-2023. Profitability has no significant effect on financial distress in food and beverage subsector companies listed on the Indonesia Stock Exchange in 2019-2023. Leverage has no significant effect on financial distress in food and beverage subsector companies listed on the Indonesia Stock Exchange in 2019-2023. The results of the F test obtained the contribution of the influence of the independent variables X1 (Liquidity / CR), X2 (Profitability) and X3 (Leverage) on Y (Financial Distress) of 84.6%. The rest (100% - 84.6%) = 15.4% is explained by other variables outside the model such as Earning Per Share (EPS), audit committee, and company size.